Long-Term Stress Disrupts the Structural and Functional Integrity of GABAergic Neuronal Networks in the Medial Prefrontal Cortex of Rats - Czéh, Boldizsár; Vardya, Irina; Varga, Zsófia; Febbraro, Fabia; Csabai, Dávid; Martis, Lena-Sophie; Højgaard, Kristoffer; Henningsen, Kim; Bouzinova, Elena V.; Miseta, Attila; Jensen, Kimmo; Wiborg, Ove (Frontiers in Cellular Neuroscience, 2018)
Clinical and experimental data suggest that fronto-cortical GABAergic deficits contribute to the pathophysiology of major depressive disorder (MDD). To further test this hypothesis, we used a well characterized rat model for depression and examined the effect of stress on GABAergic neuron numbers and GABA-mediated synaptic transmission in the medial prefrontal cortex (mPFC) of rats. Adult male Wistar rats were subjected to 9-weeks of chronic mild stress and based on their hedonic-anhedonic behavior they were behaviorally phenotyped as being stress-susceptible (anhedonic) or stress-resilient. Post mortem quantitative histopathology was used to examine the effect of stress on parvalbumin-, calretinin-, calbindin-, cholecystokinin-, somatostatin- and neuropeptide Y-positive GABAergic neuron numbers in all cortical subareas of the mPFC (anterior cingulate, prelimbic and infralimbic cortexes). In vitro, whole-cell patch-clamp recordings from layer II-III pyramidal neurons of the ventral mPFC was used to examine GABAergic neurotransmission. The cognitive performance of the animals was assessed in a hippocampal-prefrontal-cortical circuit dependent learning task. Stress exposure reduced the number of cholecystokinin-, calretinin- and parvalbumin-positive GABAergic neurons in the mPFC, most prominently in the infralimbic cortex. Interestingly, in the stress-resilient animals, we found higher number of neuropeptide Y-positive neurons in the entire mPFC. The electrophysiological analysis revealed reduced frequencies of spontaneous and miniature IPSCs in the anhedonic rats and decreased release probability of perisomatic-targeting GABAergic synapses. In turn, pyramidal neurons showed higher excitability. Anhedonic rats were also significantly impaired in the object-place paired-associate learning task. These data demonstrate that long-term stress results in functional and structural deficits of prefrontal GABAergic networks. Our findings support the concept that fronto-limbic GABAergic dysfunctions may contribute to emotional and cognitive symptoms of MDD.